Normally off Vertical 3-D GaN Nanowire MOSFETs with Inverted p-GaN Channel - Yu, Feng; Strempel, Klaas; Fatahilah, Muhammad Fahlesa; Zhou, Hao; Roemer, Friedhard; Bakin, Andrey; Witzigmann, Bernd; Schumacher, Hans Werner; Wasisto, Hutomo Suryo; Waag, Andreas (IEEE Transactions on Electron Devices, 2018)
This paper reports on the normally off GaN vertical MOSFETs based on nanowires (NWs) with an inverted p-GaN channel and a wrap-around-gate structure for the first time. Both inductively coupled plasma dry reactive-ion etching and wet-chemical etching were employed to fabricate the vertically aligned GaN NWs from epitaxial thin films with a specified doping profile. During the wet etching, the influence of p-doping on the NW morphology was investigated, and the results could be explained by the proposed model. In comparison with other c-axis NW transistors, an enhancement-mode (E-mode) operation with a superior threshold voltage ( V-th ) of 2.5 V has been reached in the fabricated GaN MOSFETs. Furthermore, a high driving-current density of 101 kA/cm2 as well as a high ON-/OFF-current ratio of 109 was obtained in the NWs, predicting a potential approach toward future GaN electronics with vertical and smart architecture.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Enhancement mode (E-mode); GaN nanowire (NW); logic circuit; MOSFET; switching; top-down; vertical transistor